JUMLAH BAKTERI COLIFORM DAN DETEKSI Escherichia coli PADA DAGING AYAM DI PEKANBARU - Usna Juwita; Yuli Haryani; Christine Jose (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Coliform bacteria are often referred as indicator organisms to indicate the potential presence of disease-causing bacteria. Escherichia coli is a type of Coliform bacteria. Most Escherichia coli are harmless and commonly found in the intestines of humans and animals. However, some strains can cause illness. Coliform bacteria and Escherichia coli contamination in chicken could be detected using Most Probable Number (MPN) multi-step assay which consists of presumptive, confirmed, and completed test. The aim of this study was to determine the number of Coliform bacteria contamination and to detect Escherichia coli in 15 chicken meat samples collected from 3 traditional markets and 3 modern markets in Pekanbaru. Estimated numbers ofColiform bacteria in samples were varied from 2.1x10 4 MPN/g to >11x10 MPN/g. We found that chicken samples were contaminated by Escherichia coli, which showed colour changes and bubles production in EC broth and the appearence of dark centered colony with metallic shine on EMB Agar.